Reproductive biology and embryology of selected alternanthera species in peninsular Malaysia / Evan Chin Hui See - Chin, Evan Hui See (2013)
Alternanthera species are perennial herbs or shrubs. A. sessilis ‘Green’ and A. ficoidea are weeds, A. sessilis ‘Red’ is a medicinal herb while A. brasiliana and A. bettzickiana are ornamental plants. All these species are introduced from tropical America except A. sessilis, which is indigenous to Malesia. The time taken for a single flower to develop from a bud to young seedling for the red and green leaf form of A. sessilis is 19–40 and 21–50 days respectively while it is 31–99 days in A. brasiliana. The anther is bisporangiate and the wall development is of the Monocotyledonous and occasionally Dicotyledonous type. Simultaneous cytokinesis during microsporogenesis resulted in mostly tetrahedral and rarely isobilateral or decussate tetrads. The mature pollen grains are shed at the three-celled stage. The ovule is campylotropus, crassinucellate and the micropyle is formed by the inner integument only. The nectar glands are located at the inner base of the filament in all the species studied except in A. brasiliana. The development of the embryo sac conforms to the monosporic Polygonum type. The fertilization is porogamous and the endosperm development is of the ab initio Nuclear type. The embryo development in A. sessilis follows the transitional form between the Chenopodiad-type and Solanad-type. Present study in the breeding system and embryology show that A. brasiliana is an obligate apomict due to cytoplasmic male sterility and early egg cell abortion. Absence of fibrous thickening in the endothecium caused anther indehiscence while absence of ubisch granules and early tapetum degeneration caused microspore abortion. The adventive nucellar embryo is without suspensor and the endosperm development is of the autonomous type. Polyembryony is occasionally noted. II Alternanthera bettzickiana is a sterile plant due to cytoplasmic male sterility and egg cell abortion. Neither coenocytic microspores nor the normal microspore tetrads develop into mature pollen grains despite the presence of the tapetum and ubisch granules. Pollen grains of Alternanthera are dodecahedric, isopolar and small. Apertures of A. sessilis and A. ficoidea are pantoporate with twelve round pores, whereas the pollen grains of A. paronychioides have eighteen oval pores. These pores are covered by rectangular, sinuous or elongated ektexinous bodies. The sexine is metareticulate and tectum perforate with unevenly distributed perforations at the top and base of the mesoporia, except in the pollen grains of A. ficoidea, in which the perforations are distributed unevenly along the microspines at the top of the mesoporia only. In A. sessilis, the optimum sucrose concentration for pollen germination in the ‘Red’ and ‘Green’ is 16% and 14–18% respectively. Pollination experiments revealed that the breeding system is facultative xenogamy and the ‘Red’ and ‘Green’ could interbreed. Thus, the result of morphology, embryology, palynology and breeding system show that A. sessilis ‘Red’ and ‘Green’ are of the same species. Both the sexually derived embryo and adventive embryo are characterized as dicotyledonous, curved and annular. The seed coat is made up of the outer layer and a small part of the inner layer of the outer integument. The seeds show epigeal germination.